Permasalahan Pengelolaan Sarana dan Prasarana dalam Pendidikan - Saputri, Icha; Fatmawati, Fifi (CV. Kurnia Grup, 2024)
Management of facilities and infrastructure is an important aspect in supporting an effective learning process. Facilities such as books, technological devices, and teaching aids, as well as infrastructure such as classrooms, laboratories, and other supporting facilities, play a role in creating a conducive learning environment. However, many educational institutions face various problems in their management, such as budget constraints, lack of routine maintenance, inefficient management, and inability to keep up with technological developments. These problems have an impact on the quality of learning and students' access to education. To overcome this, careful planning, adequate budget allocation, training for educators, and utilization of technology are needed. With these steps, the management of facilities and infrastructure is expected to run better and contribute to improving the quality of education.